Asuhan Keperawatan pada Tn. R dengan Gangguan Sistem Kardiovaskular : Hipertensi di Ruang Dahlia RSUD dr. Soeselo Kabupaten Tegal - Delfiana Aldianingsih; Tati Karyawati; Muhammad Silahudin (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Hypertension is one of the most common non-communicable diseases, with a high incidence rate that has become a major global health concern. It is often referred to as a “silent killer” because many patients are unaware of their condition until serious complications arise. In Indonesia, the prevalence of hypertension is relatively high, yet many sufferers remain undiagnosed or do not receive proper medical treatment. Several risk factors contribute to hypertension, including age, heredity, high-salt diet, obesity, lack of physical activity, and unhealthy lifestyles such as smoking and alcohol consumption. Without proper management, hypertension may lead to severe complications such as stroke, heart failure, and chronic kidney disease. Management of hypertension generally involves pharmacological therapy, such as the administration of antihypertensive drugs, as well as non-pharmacological interventions through lifestyle modifications. Nurses play a crucial role in patient education, monitoring, and preventing complications through comprehensive nursing care. The purpose of this study is to describe the nursing care provided to Mr. R, who experienced a cardiovascular system disorder, namely hypertension, in the Dahlia Ward of RSUD dr. Soeselo, Tegal Regency. The research method used was descriptive with a case study approach, allowing for a systematic and clear presentation of the patient’s condition. The case findings showed that the patient’s main complaint was a headache radiating to the nape of the neck. Based on nursing assessment, two nursing diagnoses were identified: acute pain and lack of knowledge regarding the disease and its management. Interventions were determined using national standards such as SDKI, SLKI, and SIKI, which are expected to reduce symptoms and improve the patient’s understanding of hypertension.